Enhancement of electrocatalytic activity of gold nanoparticles by sonochemical treatment - Lee, Yang-Hee; Kim, Gunn; Joe, Minwoong; Jang, Ji-Hoon; Kim, Juyeong; Lee, Kwang-Ryeol; Kwon, Young-Uk (ROYAL SOC CHEMISTRY, 2010)
We demonstrate that gold nanoparticles can become catalytically active for the electrochemical hydrogen oxidation reaction by a sonication treatment. Experimental data and theoretical calculations indicate that the activity arises from the supercooled molten state of gold nanoparticles which are enriched with coordinatively unsaturated gold atoms.
Keywords: OXYGEN REDUCTION; PLATINUM; HYDROGEN; CARBON; SIZE; IRON